Measles, mumps and rubella vaccination coverage in capitals and interior region municipalities of Northeast Brazil: a household survey in a cohort of children born in 2017 and 2018 - Adjoane Mauricio Silva Maciel; Alberto Novaes Ramos Jr; Anderson Fuentes Ferreira; Taynara Lais Silva; Carla Magda Allan Santos Domingues; Ramon da Costa Saavedra; Jaqueline Caracas Barbosa; Ana Paula França; Ligia Regina Franco Sansigolo Kerr; Maria da Gloria Teixeira; José Cássio de Moraes; Adriana Ilha da Silva; et al. (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To analyze measles, mumps, and rubella vaccination coverage among children up to 24 months old and factors associated with non-vaccination in a 2017−2018 live birth cohort, in state capitals and large interior region cities in Northeast Brazil. Methods Population-based survey analyzing vaccination coverage and sociodemographic factors through logistic regression. Results For 12,137 children, vaccination coverage was 79.3% (95%CI 76.5;81.8), and the dropout rate was 10.6%. Association with non-vaccination: socioeconomic stratum A (OR-a 1.29; 95%CI 1.10;1.50), living in the interior region (OR-a 1.22; 95%CI 1.07;1.39), no access to the Bolsa Família Program (OR-a 1.19, 95%CI 1.05;1.34), family income ≤BRL 1,000 (OR-a 1.17, 95%CI 1.03;1.31), mother not working (OR-a 1.28, 95%CI 1.15;1.42), >1 child per mother (OR-a 1.12, 95%CI 1.08;1.17), and no vaccination card (OR-a 10.69, 95%CI 6.27;18.20). Conclusion Low vaccination coverage and a high dropout rate in state capitals and municipalities in the interior region of Northeast Brazil.